2022
DOI: 10.1111/1753-0407.13286
|View full text |Cite|
|
Sign up to set email alerts
|

DUALI China: Improved glycemic control withIDegLiraversus its individual components in a randomized trial with Chinese participants with type 2 diabetes uncontrolled on oral antidiabetic drugs

Abstract: Background DUAL I China, one of the DUAL trials, assessed efficacy/safety of insulin degludec/liraglutide (IDegLira) in Chinese adults with type 2 diabetes (T2D) not controlled by oral antidiabetic drugs (OADs). Methods This phase 3a, treat‐to‐target multicenter trial randomized participants (glycated hemoglobin [HbA1c] 53.0‐85.8 mmol/mol; previous metformin ± another OAD) 2:1:1 to IDegLira (n = 361), degludec (n = 179), or liraglutide (n = 180). Primary endpoint was ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…The results presented here are fairly similar to those observed with the other approved fixed‐ratio combination preparation, IDegLira (insulin degludec [IDeg] + liraglutide [Lira]), versus IDeg or Lira in 720 Chinese participants in a recently conducted study 23,24 . After 26 weeks, mean HbA1c decreased from 66 mmol/mol (8.2%) to 48 mmol/mol (6.5%) for participants receiving IDegLira, with 77% of participants achieving HbA1c <53 mmol/mol (<7%) and 41% of participants reaching HbA1c <53 mmol/mol (<7%) without weight gain 24 .…”
Section: Discussionsupporting
confidence: 84%
“…The results presented here are fairly similar to those observed with the other approved fixed‐ratio combination preparation, IDegLira (insulin degludec [IDeg] + liraglutide [Lira]), versus IDeg or Lira in 720 Chinese participants in a recently conducted study 23,24 . After 26 weeks, mean HbA1c decreased from 66 mmol/mol (8.2%) to 48 mmol/mol (6.5%) for participants receiving IDegLira, with 77% of participants achieving HbA1c <53 mmol/mol (<7%) and 41% of participants reaching HbA1c <53 mmol/mol (<7%) without weight gain 24 .…”
Section: Discussionsupporting
confidence: 84%
“…DUALI was used in base case, while DUAL II was used for scenario analysis. Long-term projections of costs and clinical outcomes based on data from the DUALI [ 17 ] and DUALII [ 16 ] China clinical trial study were made using the IQVIA CORE Diabetes Model Version 9.0 (IQVIA, Basel, Switzerland), a previously published and validated model of type 2 diabetes [ 18 20 ]. The non-product-specific diabetes policy analysis tool is capable of conducting real-time simulations that incorporate different treatment regimens.…”
Section: Methodsmentioning
confidence: 99%
“…The LixiLan series studies and the DUAL series studies have verified the efficacy and safety of Insulin Glargine–Lixisenatide FRC and Insulin Degludec–Liraglutide FRC, respectively, in patients with T2DM. These FRC regimens have been confirmed to improve glucose levels in patients whose glycemic control cannot be well regulated with oral glycemic drugs, basal insulin, or GLP‐1RAs 120–125 . Post hoc analysis of the LixiLan‐L/O study and multiple DUAL series studies have indicated that, compared with therapies with a single component, Insulin Glargine–Lixisenatide FRC and Insulin Degludec–Liraglutide FRC are effective, safe, and tolerable in older patients 116,117,126 …”
Section: Chapter 8: Glycemic Medications and Treatment Strategies For...mentioning
confidence: 99%
“…These FRC regimens have been confirmed to improve glucose levels in patients whose glycemic control cannot be well regulated with oral glycemic drugs, basal insulin, or GLP‐1RAs. 120 , 121 , 122 , 123 , 124 , 125 Post hoc analysis of the LixiLan‐L/O study and multiple DUAL series studies have indicated that, compared with therapies with a single component, Insulin Glargine–Lixisenatide FRC and Insulin Degludec–Liraglutide FRC are effective, safe, and tolerable in older patients. 116 , 117 , 126 …”
Section: Chapter 8: Glycemic Medications and Treatment Strategies For...mentioning
confidence: 99%